2006
DOI: 10.1590/s1678-77572006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed tooth replantation after root surface treatment with sodium hypochlorite and sodium fluoride: histomorphometric analysis in rats

Abstract: In cases of delayed tooth replantation, non-vital periodontal ligament remnants have been removed with sodium hypochlorite in an attempt to control root resorption. Nevertheless, reports of its irritating potential in contact with the alveolar connective tissue have been described. Therefore, this study evaluated the healing process on delayed replantation of rat teeth, after periodontal ligament removal by different treatment modalities. Twenty-four rats, assigned to 3 groups (n=8), had their upper right inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…, Sottovia et al . ); however, the optimal concentration and working time of NaOCl were not determined in these studies. The present results showed that, consistent with previous studies, the necrotic PDL‐dissolving efficacy of NaOCl solution was enhanced by increasing its concentration and extending the working time, but these changes also increased damage to the root surface and cementum.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…, Sottovia et al . ); however, the optimal concentration and working time of NaOCl were not determined in these studies. The present results showed that, consistent with previous studies, the necrotic PDL‐dissolving efficacy of NaOCl solution was enhanced by increasing its concentration and extending the working time, but these changes also increased damage to the root surface and cementum.…”
Section: Discussionmentioning
confidence: 95%
“…, Sottovia et al . ). However, the proper combination of concentration and working time for NaOCl application for PDL removal and its effects on the cementum layer are unknown.…”
Section: Introductionmentioning
confidence: 97%
“…However, it is not known whether this necrotic tissue should be removed or not before replantation and how this should be performed. There have been suggestions for various substances for topical application on the root surface or in the root canal prior to replantation of teeth with long extra-oral periods (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, current recommendations for clinical management of teeth with long extra-oral storage are still mainly based on best practice experience (16).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have been used but also have limitations in availability (25,(33)(34)(35). Mice are more accessible for in vivo experiments (22,26,27,29). However, one must be aware that with smaller animals, the tissue reactions may differ from monkeys and humans.…”
Section: Discussionmentioning
confidence: 99%
“…These include using a scalpel blade, 22 rubber cup polishing with pumice/water slurry, 23 diamond bur and sandpaper disk 24 or chemically with sodium hypochlorite solution. 25,26 With regard to the removal of necrotic root PDL using sodium hypochlorite, the authors who employed the chemical removal with sodium hypochlorite justify its use because this technique preserves the cementum layer, 25,26 which is an important barrier against the external root resorption. However, although such measures may have an advantage after short-term healing, it has been shown that ankylosis and osseous replacement of the tooth still occur even if the cementum layer is intact.…”
Section: Current Recommendations For Clinical Management Of Avulsedmentioning
confidence: 99%